Difficulties in Learning English Speaking of Senior High School Students - Jannah, Miftahul; Ilma, Ridha; Yani, Ahmad (IJER (Indonesian Journal of Educational Research), 2023)
The acquisition of speaking proficiency continues to be a significant challenge for a majority of individuals learning the English language. There are various factors that can contribute to students having difficulty speaking in English. The purpose of this research was to find out the students’ problems in learning English speaking skills. A qualitative descriptive method was the design of the study. Two students of the eleventh grade of one of Islamic senior high school in Palembang became the subject of the study, and interview was the instrument to collect the data. The results showed that students’ difficulties consisted of linguistic problem such as lack of grammar mastery, lack of pronunciation mastery and lack of vocabulary mastery, and psychological problem such as fear of making mistake, feeling shy, feeling anxious, lack of confidence and lack of motivation.